Effect of planned teaching programme on knowledge and practices in relation to diet and fluid management among hemodialysis patients of selected hospitals - Jadhav, Natasha (International Journal of Nursing Research, 2023)
Background and Aim: The role of nutrition in improving health conditions in patients undergoing hemodialysis is known. It is unknown whether education can play important role in improving knowledge and dietary practices in the patients undergoing hemodialysis. Patient and Methods: A total of 30 patients were enrolled from dialysis units of MGM hospital and Medical College Kamothe and MGM New Bombay Hospital, Vashi. Results: The study observed that planned teaching programme significantly improved knowledge score and dietary practices score in the patients. Conclusion: Education can be an important tool to improve the patients' knowledge.